Progress of Pathogenesis in Pediatric Multifocal Atrial Tachycardia - Chen, Huaiyang; Ma, Yingxu; Wang, Yefeng; Luo, Haiyan; Xiao, Zhenghui; Chen, Zhi; Liu, Qiming; Xiao, Yunbin (Frontiers in Pediatrics, 2022)
Multifocal atrial tachycardia (MAT) is defined as irregular P-P, R-R, and P-R intervals, isoelectric baseline between P waves, and ventricular rate over 100 beats/min. Although prognosis of pediatric MAT in most patients is favorable, adverse outcomes of MAT have been reported, such as cardiogenic death(3%), respiratory failure(6%) or persistent arrhythmia(7%), which due to delayed diagnosis and poorly controlled MAT. Previous studies demonstrated that pediatric MAT is associated with multiple enhanced automatic lesions located in the atrium or abnormal automaticity of a single lesion located in the pulmonary veins via multiple pathways to trigger electrical activity. Recent studies indicated that pediatric MAT is associated with formation of reentry loop, abnormal automaticity, and triggering activity. The occurrence of pediatric MAT is affected by gestational disease, congenital heart disease, post-cardiac surgery, pulmonary hypertension and infectious diseases, which promote MAT via inflammation, redistribution of autonomic nervous system, and abnormal ion channels. However, the pathogenesis of MAT needs to be explored. This review is aimed to summarize and analyze the pathogenesis in pediatric MAT.